Corrosion of high chromia refractory materials by basic coal slag under simulated coal gasification atmosphere. Issue 5 (1st April 2018) - Cai, Binli; Li, Hongxia; Zhao, Shixian; Sun, Honggang; Li, Pengtao; Yan, Shuangzhi; Du, Yihao; Wang, Gang; Cao, Zhanmin
Abstract: In this paper, dynamic corrosion experiment of a high chromia refractory interaction with basic coal slag under slagging gasifier conditions was conducted by using rotary drum corrosion test with the FactSage thermodynamic analysis. The microstructures and chemical compositions of the corroded samples were analyzed by scanning electron microscopy (BEI and EDS), and the corrosion mechanism was investigated by combining thermodynamic simulation and SEM analysis. The results show that the simulation results were consistent with the results of corrosion test. Reaction layer and penetration layer are formed from the surface to the interior of the sample after corrosion. The (Mg, Fe) (Al, Cr)2 O4 spinel solution was formed in the reaction layer, which make the matrix structure become dense and change the overall structure of the particles' uniformity. Corrosion of Cr2 O3 aggregate is relatively weak by slag. The Cr2 O3 dissolves into the slag through the formed spinel solution layer on the surface of aggregates. While, Cr2 O3 and Al2 O3 dissolve into molten slag through the spinel solution layer formed in the matrix. ZrO2 in the matrix directly dissolved into molten slag and penetrates inner the matrix with the penetration of the slag to form a ZrO2 -free region. The liquid sintering of the matrix has happened in the melt, causes the structure of the penetration layer become dense, which is different from that of the original sample.